Cyclotron radiation of semiconductor crystals - Milenin, G.V.; Milenin, V.V.; Red'ko, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2018)
We obtained relations for estimating the power of cyclotron radiation of semiconductor crystals when the plasma of thermal carriers is not in a state of thermodynamic equilibrium. It has been shown that the radiation power is a power function of the magnetic field induction. The theoretical calculations are in good agreement with the experimental results.